Green Architecture for Sustainable Hotel Design in Sosromenduran - Raden Zoland Bintang Permanaa; Endy Marlina; Desrina Ratriningsih (Universitas Teknologi Yogyakarta, Yogyakarta, Indonesia, 2025)
Yogyakarta is a major tourism destination undergoing rapid expansion of hotel and tourism infrastructure, resulting in increased environmental pressures such as greenhouse gas emissions, rising temperatures, and urban pollution. These impacts of global warming underscore the need for environmentally responsible development in the hospitality sector, positioning Green Architecture as a strategic approach to achieving sustainable tourism development. This study aims to explore the implementation of Green Architecture principles in hotel design as a means of reducing environmental impacts while meeting the growing demand for accommodation in Yogyakarta. The research employs a qualitative, design-based approach by integrating green architectural strategies into the planning and design process. Key strategies include optimizing building orientation and massing in response to solar patterns, maximizing natural ventilation and daylighting, integrating photovoltaic systems as renewable energy sources, and applying rainwater harvesting to supplement water supply and reduce groundwater exploitation. Landscape design and green spaces are also emphasized to improve microclimate conditions and thermal comfort. The results demonstrate that the proposed Green Architecture approach can enhance energy efficiency, reduce reliance on mechanical ventilation and artificial lighting, and improve indoor and outdoor environmental comfort. However, this study is limited to a conceptual design framework and does not include post-occupancy or operational performance evaluation. Future research is recommended to assess long-term energy and water savings and user comfort to strengthen the practical application of Green Architecture in hotel development.